Impact on participation and autonomy: test of validity and reliability for older persons - Isabelle Ottenvall Hammar; Christina Ekelund; Katarina Wilhelmson; Kajsa Eklund (Health Psychology Research, 2014)
In research and healthcare it is important to measure older persons’ self-determination in order to improve their possibilities to decide for themselves in daily life. The questionnaire Impact on Participation and Autonomy (IPA) assesses self-determination, but is not constructed for older persons. The aim of this study was to examine the validity and reliability of the IPA-S questionnaire for persons aged 70 years and older. The study was performed in two steps; first a validity test of the Swedish version of the questionnaire, IPA-S, followed by a reliability test-retest of an adjusted version. The validity was tested with focus groups and individual interviews on persons aged 77-88 years, and the reliability on persons aged 70-99 years. The validity test result showed that IPA-S is valid for older persons but it was too extensive and the phrasing of the items needed adjustments. The reliability test-retest on the adjusted questionnaire, IPA-Older persons (IPA-O), showed that 15 of 22 items had high agreement. IPA-O can be used to measure older persons’ self-determination in their care and rehabilitation.